HAS SECULARISM FAILED AS A CONCEPT IN INDIA? - A STUDY - Pasha, S. Ameer (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present paper purports to examine and analyze the concept of Secularism in the context of world in general and India in particular. India is a secular state in the same way as it is a democratic state. Secularism is the only way of development in a plural society like ours. It is not a new phenomenon in India, we find its roots in the reign of Asoka the Great. But the occurrence of communal riots in the recent years indicates that the Indian Government has failed to establish a secular society. Communal politics, religious militancy, poverty, illiteracy and political corruption are posing serious threats to secularism. But the present turmoil will certainly be ever if sincere efforts with more stable secular policy are made. Majority of the problems will automatically be solved and the country will become an abode of peace progress and prosperity.